Enacting inclusive practices in STEM environments by engaging STEM faculty in self-reflexivity - Beverly, Selyna Pérez (Frontiers in Education, 2025)
IntroductionIntegrating self-reflexive work in STEM faculty professional development that interrogates aspects of identity, power, and privilege can lead to inclusive practices within the classroom and beyond. The purpose of this study is to examine the effects of purposefully centering self-reflexive processes focused on identity to create more inclusive STEM faculty.MethodsThe NSF Eddie Bernice Johnson INCLUDES Aspire Alliance Summer Institute (ASI) was a week-long summer intensive program geared toward faculty, institutional leaders, and faculty developers to learn how to support STEM faculty and higher education leaders in engaging in inclusive practices centered on an equity mindset. In this study, interviews were conducted with twelve faculty (tenure and non-tenure track) from a variety of STEM disciplines from the 2021–2023 cohorts. Participants were asked about their learning experiences in the ASI and what they did with the knowledge they gained.ResultsFindings indicate that self-reflection activities, focused on social identity, moved participants toward self-reflexivity in which they were made more aware of their power and privilege. Participants also discussed how their identity awareness contributed to changes in their teaching practices as well as their relationships with students and colleagues. Finally, participants that were already aware of their identity continued to engage in inclusive practices in STEM, further deepening their awareness.DiscussionThis work reveals that having STEM faculty critically reflect on their identity leads to self-reflexivity, a recognition of power and privilege in various contexts, thus creating a pathway to more inclusive learning conditions for underrepresented students in STEM. This research further indicates that self-reflexivity can also contribute to inclusive practices beyond the classroom in other environments, impacting how people interact with others in their daily work.